KNOWLEDGE AND PRACTICE OF CARING WHEN CHILDREN HAVE DIARRHEA OF MOTHERS WITH CHILDREN AGED 6-24 MONTHS IN MINH KHAI COMMUNE, HOAI DUC DISTRICT, HANOI (Vietnam Journal of Community Medicine, 2022)
Objectives: Describe the knowledge and practice of caring when children have diarrhea of mothers with children aged 6-24 months in Minh Khai commune, Hoai Duc district, Hanoi.Materials: 216 mothers with children aged 6-24 months in Minh Khai commune, Hoai Duc district, Hanoi.Methods: Cross-section DescriptionResults: Through a survey of 216 mothers in Minh Khai commune, the percentage of mothers with knowledge of caring for children with diarrhea was 63.4% and 36.6% of mothers did not have knowledge when taking care of children with diarrhea. Out of 216 children born to mothers, only 171 children ever had diarrhea, accounting for 79.2%. When the child had diarrhea in the last time, 59.7% of mothers cared for at home and 10.2 mothers sent the child to the health station. The practice of mothers taking care of children with diarrhea has 46.8% passed and 53.2% failed out of 171 mothers who had to take care of their child with diarrhea in the last time.
Keywords: Diarrheal diseases, mothers, knowledge, practice, caring.